THE EFFECT OF RETURN ON ASSETS RATIO, DEBT TO EQUITY RATIO ON THE VOLATILITY OF SHARE PRICES OF COMPANIES IN INDONESIA THAT ARE MEMBERS OF ESG-BASED STOCK INDICES - Yefta Trifosa Meliala (Sean Institute, 2023)
Stocks are one of the popular investment instruments among investors. Investors widely choose this stock investment instrument because it can provide attractive returns higher than other investment instruments. However, stocks in addition to providing high returns, have high risks as well. This study aims to determine the effect of ROA and DER on the volatility of stock prices of companies in Indonesia that are members of the ESG-based DAHAM index. This quantitative research uses ROA and DER variables on stock price volatility. The application of research objects is carried out in public companies in Indonesia that are incorporated into ESG-based indices. This study’s results state that ROA does not affect price volatility. And the inclusion of companies in ESG-based indices indicate that companies have good ESG scores but does not necessarily increase the company's ROA. DER significantly negatively influences share price volatility in companies incorporated into ESG-based stock indices. And ROA and DER simultaneously affect stock price volatility, but only explain 12.9% of stock price volatility.